Effects of Servicescapes on Diner Satisfaction and Behavioral Intentions in Family Chain Restaurants - Goodarzirad, Bahar (2010)
Servicescapes are important tangible elements of the service organizations that provide cue to customers and create an immediate perceptual image in their minds. Many previous studies reported factors that influence preferences in restaurant settings, which reinforce the need for further studies in the field in order to create more meaningful environments from customers‟ perspective. This study dealt with factors related to the servicescapes of family chain restaurants, which enhance the dining experience. The objectives were to identify the various attributes of servicescapes, to find out which dimension of servicescapes has the most impact on diners‟ overall satisfaction, to measure the probability of return as a consequence of dining satisfaction and, to determine the influence of color within servicescapes. The study also encompasses the dimensions of servicescapes such as facility aesthetics, layout accessibility, seating comfort, ambient condition, and cleanliness as the most prominent influences on diners overall satisfaction towards family chain restaurants. Employing the performance-only approach, this study investigates Malaysian diners‟ perceptions of satisfaction towards servicescapes of family chain restaurants in Klang Valley. In addition, in this study special attention has been given to the impact of color within servicescapes as it can contribute to a differentiation of service environment among various restaurants, thus influencing customers‟ pleasure feelings and behavioral intentions. Data gathered through the convenient sampling of family chain restaurant customers using a structured self-administrated questionnaire to Malaysian restaurant diners. Survey questionnaire was developed based on items identified by previous researches. Descriptive analysis, Confirmatory Factor Analysis,Measurement Model and Structural Model (Path analysis) were performed during data analysis using the SPSS (Statistical Package for the Social Sciences) and AMOS (Analysis of Moment Structure). Nine hypotheses were derived and the analysis found that all nine were supported. Key findings include the important role of functional and effective servicescapes components in shaping customer satisfaction and future patronage intentions. The results of the analysis suggested that there were a significant positive relationship between servicescapes dimensions and their level of satisfaction and that satisfaction with the dining event does lead significantly to repeat patronage and also mediates these relationships. Each of the servicescapes dimensions was identified as the determining attributes which strongly predicted the satisfaction as well as the important roles they played in the formation of customer post dining behavior. Moreover, facility aesthetics emerged as the most highly correlated variable followed by cleanliness. This study also found that color an aspect of servicescapes as stimuli that enhance pleasure feeling in consumption experience and in turn impact diner behavioral intentions in the family chain restaurants. Findings of the study revealed that facility aesthetics (color as sub-dimension) and cleanliness are the two important aspects where family chain restaurants can enhance their innovation and creativity. The restaurant managers must maximize the effects of servicescapes to further enhance customer satisfaction by reasonably allocating their limited resources to enrich restaurant attributes due to the importance of their contribution to customer satisfaction and behavioral intentions. Findings also show that colors play persuasive roles in forming feelings and behaviors, which necessitate that managers understand the important role of colors in marketing services. This study is designed to contribute to the debate. Future research could concentrate on determining effects of servicescapes attributes on customers and also employees, in other sectors of Malaysian restaurants.Keywords: diner satisfaction; behavioral intention; servicescapes; family chain restaurants; color; pleasure feeling, Malaysia.